Analysis of flow parameters in blood flow through mild stenosis - Pokharel, Chudamani; Gautam, Pushpa Nidhi; Tripathee, Samundra Timilsina; Bhatta, Chet Raj; Kafle, Jeevan (Nepalese Journal of Zoology, 2022)
A buildup of plaque that contracts arteries and decreases blood flow to the heart causes chest pain, difficulties in breathing, or another coronary artery disease, medically called stenosis puts our lives at risk. We have used Navier-Stokes equations in a cylindrical polar coordinate system to study this problem by considering the flow is steady, axially symmetrical, fully developed, and laminar. Flow parameters like velocity profile, pressure drop, shear stress, and volumetric flow rate in the stenosed regions are analyzed after getting analytical solutions. We have focused our study to know the effect of the thickness of the stenosis in different parameters and the effect of the viscosity coefficient on blood flow behavior.